(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, pre-school education is to educate the organization of the pedagogical significance of the implementation of technology based on the process of knowing neyrotarmoq and characteristics to emphasize lit. Comprehensive education and training them in the process of nurturing personality o‘rga their capabilities to take into account a number of features highlighting with neurologic psixofiziologik was. Education by assisting in the development of programs to educate teachers and coaches struggling ahmaiyatli particular attention is lit.. Education and training of the applicant in the process of education is a comprehensive approach to take into account the comprehensive capabilities and deep knowing and neurologic.